Kepemimpinan Agama Dan Dialog Antaragama: Strategi Pembangunan Masyarakat Multikultural Berbasis Moderasi Beragama - Amtiran, Abdon Arnolus; Kriswibowo, Arimurti (Jurnal Penelitian Agama Hindu, 2024)
This research discusses the important role of religious moderation and interfaith dialogue in building a tolerant multicultural society. Using a qualitative approach, specifically through observation and complex literature study, this research explains the close relationship between religious moderation, interfaith dialogue, and the development of a multicultural society. Through theoretical and practical analysis, this research focuses on examining the synergy between religious leadership and interfaith dialogue as effective strategies in implementing religious moderation within the context of a multicultural society in Indonesia, and addressing challenges arising from religious differences. It emphasizes the importance of moderate religious education, the role of religious figures, and strategies of interfaith dialogue in creating harmony amidst religious differences. Findings of this research include: firstly, religious moderation as a principle that is fair, balanced, and tolerant, is key to preventing conflicts and maintaining harmony in a multicultural society. Secondly, the strategic role of religious leadership in promoting religious moderation through inclusive religious education, development of tolerance, and interfaith dialogue. Thirdly, the need for interfaith dialogue to create understanding and respect for religious freedom, as well as to strengthen tolerance through open and constructive interactions. Lastly, the importance of integrating religious moderation values into the curriculum of religious education is essential in shaping a moderate younger generation and supporting the development of a harmonious multicultural society. The conclusion of this research underscores the need for synergy between religious leadership and interfaith dialogue in promoting religious moderation. Interfaith dialogue and moderate religious education are found to be the main pillars in creating a tolerant and harmonious society. Through the integration of religious moderation in education and religious practices, a multicultural society will be able to develop attitudes that are more inclusive, tolerant, and accepting of differences.